Four levers of redistribution: The impact of tax and transfer systems on inequality reduction - Elvire Guillaud; Matthew Olckers; Michaël Zemmour (Luxembourg Income Study (LIS), 2017)
Using observational micro data from the Luxembourg Income Study (LIS), we assess the redistributive impact of tax and transfer configurations across 22 OECD countries for the period 1999-2013. After recovering new tax data (employer social contributions), we measure the reduction of income inequality due to the four structural dimensions of tax and transfer systems: the average tax rate, tax progressivity, the average transfer rate, and transfer targeting. Among the most remarkable results, we notice (i) the diverse combinations of taxation and transfers that achieve the same reduction in inequality; (ii) the absence of configurations that match strongly progressive taxation with a high rate of taxation; and (iii) the decisive impact of the rate of transfers relative to targeting.
Keywords: H23; H55; I38; 330; tax-benefit system; inequality reduction; social protection; redistributive policies